2020
DOI: 10.1021/acs.jchemed.0c00729
|View full text |Cite
|
Sign up to set email alerts
|

Responses to the COVID-19 Pandemic by the Biochemistry Authentic Scientific Inquiry Lab (BASIL) CURE Consortium: Reflections and a Case Study on the Switch to Remote Learning

Abstract: Campus shutdowns during the SARS-CoV-2 pandemic posed unique challenges to faculty and students engaged in laboratory courses. Formerly hands-on experiments had to be quickly pivoted to emergency remote learning. While some resources existed prior to this period, many currently available online modules and/or simulations focus on a single technique. The Biochemistry Authentic Scientific Inquiry Lab (BASIL) curriculum has, for several years, provided a robust, linked, holistic inquiry experience that allows stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Motivation was perceived to decrease for the students who had to rely on others’ data rather than their own. 92 Eighty-one percent of responding analytical chemistry students in two different courses at Complutense University (Madrid, Spain) (46% response rate combined), where they watched videos, analyzed sample data, and presented orally to the class, preferred f2f over remote, although they still rated their instructors and the teaching favorably. 84 …”
Section: Student Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivation was perceived to decrease for the students who had to rely on others’ data rather than their own. 92 Eighty-one percent of responding analytical chemistry students in two different courses at Complutense University (Madrid, Spain) (46% response rate combined), where they watched videos, analyzed sample data, and presented orally to the class, preferred f2f over remote, although they still rated their instructors and the teaching favorably. 84 …”
Section: Student Outcomesmentioning
confidence: 99%
“…Biochemistry CURE instructors at five American institutions also predicted that their students would have been less successful in the remote portion of the course if they had not had their earlier f2f experiences; this prediction is tentatively supported by a comparison to historical data, which showed student learning gains in knowledge–experience–confidence were lower than for previous students. 92 A survey of physics students at five universities in Europe also found that, of 220 students who reported that their laboratories transitioned to an online format, the first-year students were significantly more likely than second-year students to report that the remote laboratories did not help them develop experimental skills; 135 presumably the second-year students felt they had greater development partly because they were able to use their prior knowledge in laboratories to extract useful information from their remote learning. Tellingly, the type of student did not significantly differ in their perception of their content knowledge development.…”
Section: Considering the Role Of Prior F2f Laboratoriesmentioning
confidence: 99%
“…The COVID-19 pandemic has almost ended the historical debate on whether we should broadly engage students in computer supported inquiry learning (CoSIL). An increasing number of educators has started to realize the critical merit of CoSIL when participating in in-person scientific practices with students is not viable (Sikora et al 2020 ). CoSIL allows students to investigate phenomena and figure out problems in virtual environments which are safe, low-cost, and self-paced; however, CoSIL is also highly self-regulated and requires guidance for students to feasibly and deeply engage in virtual activities.…”
Section: Impact and Valuementioning
confidence: 99%
“…An effective biochemistry laboratory could facilitate the strengthening of concept learning [3]. Ideally, the laboratory exercises should be designed to promote students to be able to formulate question related to the observed-phenomenon, capable to design and carryout an experimental strategy, to collect and critically analyse the results, to reach conclusion, and to decide whether further experiments should be conducted to answer the questions or new additional questions that may have come from the investigations [4].…”
Section: Introductionmentioning
confidence: 99%